2003
DOI: 10.4141/s01-037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of digital terrain modelling for quantifying the spatial variability of 2,4-D sorption by soil within agricultural landscapes

Abstract: Farenhorst, A., Florinsky, I. V., Monreal C. M. and Muc, D. 2003. Evaluating the use of digital terrain modelling for quantifying the spatial variability of 2,4-D sorption by soil within agricultural landscapes. Can. J. Soil Sci. 83: 557-564.The most sensitive input parameter in many herbicide fate and transport models is the sorption-partitioning coefficient (Kd), a measure of herbicide sorption by soil. Spatial analyses of Kd are traditionally performed using geostatistics, but this approach requires intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…This is in agreement with the findings of previous studies in which soil organic carbon content was the primary factor influencing 2,4-D sorption in surface soil, both in field and laboratory experiments (Hermosin and Cornejo 1991;Mallawatantri and Mulla 1992;Johnson et al 1995;Farenhorst et al 2003). The A horizon had significantly greater capacity to sorb the herbicide relative to the B *, **, and *** denote P < 0.05, P < 0.01, and P < 0.001 level of significance, respectively, for correlations Ho: r = 0; Ha: r ≠ 0.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the findings of previous studies in which soil organic carbon content was the primary factor influencing 2,4-D sorption in surface soil, both in field and laboratory experiments (Hermosin and Cornejo 1991;Mallawatantri and Mulla 1992;Johnson et al 1995;Farenhorst et al 2003). The A horizon had significantly greater capacity to sorb the herbicide relative to the B *, **, and *** denote P < 0.05, P < 0.01, and P < 0.001 level of significance, respectively, for correlations Ho: r = 0; Ha: r ≠ 0.…”
Section: Discussionsupporting
confidence: 93%
“…Herbicide persistence and mobility may vary in field soils as sorption processes respond to the heterogeneity of soil properties that exists across slope positions and with soil depth (Jacobsen et al 2001;Strebe and Talbert 2001;Farenhorst et al 2003). Factors that affect the variation of soil properties across slope positions and with soil depth include soil pedogenic factors, such as the influence of topography on hydrologic processes, and irregularities in parent material deposition (Goderya 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive linear relation between SOC and 2,4-D Kd, as observed for other surface and subsurface soils in agricultural fields (Farenhorst et al, 2003;Gaultier et al, 2006;Farenhorst et al, 2008). This is not surprising because soil organic carbon content is the primary factor influencing 2,4-D sorption (Reddy and Gambrell, 1987;Mallawatantri and Mulla, 1992;Hermosin and Cornejo, 1993;Johnson et al, 1995).…”
Section: Discussionsupporting
confidence: 49%
“…Sorption coefficients (measures of pesticide sorption by soil) are among the most sensitive input parameters in pesticide fate models. It has been demonstrated that sorption coefficients (K d ) vary within soil landscapes due to differences in soil organic carbon (SOC) content or soil pH between slope positions (Novak et al, 1997; Farenhorst et al, 2003). Establishing methods to account for this variation could reduce uncertainties in regional‐scale assessments of pesticide fate (Dubus et al, 2003).…”
Section: Description Of Terrain Attributesmentioning
confidence: 99%